Sheep farms in the Spanish rangelands (dehesas): Typologies according to livestock management and economic indicators - Gaspar, P; Escribano, M; Mesías, F J; Ledesma, a. Rodriguez De; Pulido, F (Small Ruminant Research, 2008)
Forty-six dehesa sheep farms of Extremadura (SW Spain) were analyzed on the basis of previously determined technical and economic indicators. A principal component analysis gave ﬁve principal components – related to intensiﬁcation, proﬁtability, and livestock mix – that characterized the farms. Using multivariate techniques based on these factors, a farm typology was established with six categories—three of sheep alone at different levels of intensiﬁcation, and three of sheep in combination with beef cattle or Iberian pig. This typology enabled homogeneous groups of farms to be considered for possible administrative actions relating to their optimal dimensions and stocking rates
Keywords: Dehesa; Farm typology; Principal component analysis; Sheep; technical and economic management